Dynamic Effort Choice in High School: Costs and Benefits of an Academic Track - De Groote, Olivier (Journal of Labor Economics, 2025)
I investigate high school tracking policies using a dynamic discrete choice model of study programs and unobserved effort. I estimate the model using data from Flanders (Belgium) and perform an ex-ante evaluation of a policy that encourages underperforming students to switch to less academically ori-ented programs. This reduces grade retention by a third and dropout by 11%. Although it decreases college enrollment, the decrease in college graduation is small and insignificant. I also show that modeling effort is important, otherwise we would predict smaller decreases in grade retention and dropout and larger decreases in college enrollment and graduation.